PENINGKATAN HASIL BELAJAR MATEMATIKA TEMA PENGALAMANKU MENGGUNAKAN MEDIA KONKRET PADA SISWA KELAS I SEKOLAH DASAR - Sukriadi Sukriadi; Wulan Karmila; Mohammad Siddik; Mustamiroh Mustamiroh; Kusdar Kusdar (Universitas Pakuan, 2021)
INCREASING MATHEMATICS LEARNING RESULTS THEMES OF MY EXPERIENCE USING CONCRETE MEDIA IN 1ST CLASS ELEMENTARY SCHOOLThis study aims to determine the improvement of mathematics learning outcomes in my experience theme after applying learning using concrete media. This type of research is Classroom Action Research (CAR). The research was conducted in two cycles and each cycle consisted of two meetings. The research procedure consisted of four stages, namely, planning, implementation, observation, and reflection. Data collection techniques in this study using observation and tests. The research instrument used teacher activity observation sheets, student activity observation sheets, and evaluation test questions. The data analysis technique in this study uses the calculation of the average, percentage, and graph. The results obtained from the initial average score of 51.71 students increased in the first cycle of 72.04 with the percentage increase in the initial value of 17.86% to 39.29%, the second cycle of 87.20 with the percentage increase to 85.71%. Thus, it can be concluded that the use of concrete media on the theme of my experience in mathematics can improve the learning outcomes of first grade students at SD Negeri 008 Samarinda Ulu.